Prognostic Value of Inflammatory Markers in Septic Critically Ill Patients with Chronic Liver Disease: A Retrospective Analysis* - Boyacı Dündar, Nazlıhan; İnci, Kamil; Aygencel, Gülbin; Türkoğlu, Melda; Gökçe, Onur; Cindoruk, Mehmet (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Septic patients with chronic liver disease (CLD) experience high morbidity and mortality rates, particularly in the intensive care unit (ICU) setting, due to immune dysfunction. Despite their vulnerability, data on prognostic markers remain scarce, particularly when assessed in conjunction with disease severity scores. This study aimed to evaluate the prognostic value of various inflammatory markers, including white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), lactate, and lactate-to-albumin ratio (LAR), in septic critically ill CLD patients. Materials and Methods: A retrospective cohort study was conducted on 126 septic CLD patients admitted to ICU. Data on demographics, clinical scores, inflammatory markers, and clinical outcomes were collected. Logistic regression and ROC analyses were used to identify independent predictors of ICU mortality. Results: Intensive care unit mortality was 66%. In addition to higher Acute Physiology and Chronic Health Evaluation II (APACHE II) (39.3 Å} 7.2 vs. 21 Å} 5.1, P < .001), Sequential Organ Failure Assessment (12.4 Å} 3.5 vs. 8.5 Å} 3.1, P < .001), CLIF-C ACLF [63 (54-69) vs. 50 (41-53)] scores, ICU non-survivors had higher WBC (median: 14 400/μL vs. 7300/μL, P < .001), lactate (median: 4.6mmol/L vs. 2.4mmol/L, P < .001), NLR (median: 12.5 vs. 9, P = .015), and LAR (median: 2.15 vs. 0.93, P < .001) compared to survivors. Multivariate analysis identified APACHE II (OR 1.183, 95% CI: 1.003-1.396, P = .046), CLIF-C ACLF (OR 1.104, 95% CI: 1.002-1.216, P = .046), and LAR (OR 2.992, 95% CI: 1.277-7.009, P = .012) as independent predictors of ICU mortality. The LAR was the most significant inflammatory marker (area under the curve: 0.783, cut-off: 1.17), even in the subgroup of patients with low acute decompensation scores based on the CLIF-C ACLF score. Conclusion: The LAR was a valuable prognostic marker for ICU mortality in septic CLD patients, even in the absence of advanced organ failure. This marker potentially outperforms other traditional inflammatory markers and could aid in early risk stratification for critically ill septic CLD patients. Cite this article as: Boyacı Dündar N, İnci K, Aygencel G, Türkoğlu M, G.k.e O, Cindoruk M. Prognostic Value of Inflammatory Markers in Septic Critically Ill Patients with Chronic Liver Disease: A Retrospective Analysis. Turk J Gastroenterol. 2025;36(9):600-608.